The effect of circuit games on manipulative movement for elementary school students aged 9-10 years - Fika Widiana Kuspratiwi; Wawan Sundawan Suherman; Amat Komari (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Objective. The purpose of this study was to analyze the effect of circuit games on improving manipulative motor skills in elementary school students aged 9-10 years based on gender.